Educational and cultural experiences of migrant meskhetian Turkic students in Turkish school settings - ALPAYDIN, YUSUF (My University, 2022)
The study aims to provide insights into Turkish national education policies toward immigrant communities based on the experiences of Meskhetian Turkic high school students who migrated to Turkey. The study was done qualitatively and carried out via in-depth interviews with 10 Meskhetian Turkic students attending 12th grade at various high schools in Istanbul. According to the findings of the research, students sometimes felt discriminated against and had difficulty expressing themselves because they did not know the local language. Participants perceived teachers as having an inclusive attitude but commented that they could not get enough support from the guidance service. Meskhetian students stated that they needed to be better supported financially and believe that they should be included in the school activity calendar and cultural studies to promote their culture. Educational policymakers should be aware that ensuring positive educational experiences for historically interconnected communities like Meskhetians will help future economic, social, and political cooperation.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; Science, Technology and Society; SİYASET BİLİMİ; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); POLITICAL SCIENCE; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Siyasi bilimler ve Uluslararası İlişkiler; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; General Social Sciences; Social Sciences & Humanities; Meskhetian Turks; Migration; Education; Culture; Policy; Meskhetian Turks; Migration; Education; Culture; Policy